Social responsibility in non-investor-owned organisations. Issue 2 (4th February 2020) - Sacchetti, Silvia; Tortia, Ermanno
Abstract : Purpose: This study investigates how the creation of social value occurs in different organisational fields, and how it is implemented by organisations that are typically associated with member welfare and social objectives. The purpose of this study, specifically, is to analyse how social responsibility is implemented in organisational forms that do not pursue profit-making objectives in an exclusive or dominant way, that is, organisations that explicitly shape their aims and governance around the production of social value. Design/methodology/approach: The paper discusses the main types of organisational forms and their relation with social responsibility. It then presents four case studies completed between 2011 and 2013 in Scotland, UK. These include a range of types of non-investor-owned organisations: two employee-owned companies, one co-operative enterprise and one social enterprise. The case studies have explanatory and descriptive nature, and were aimed at enquiring how non-conventional organisations design their governance, achieve economic sustainability and show capacity to produce social value. Findings: Findings highlight the most common elements of the modality by which social responsibility is instituted in the non-profit sector. These include: modifying control rights ("who takes part" and "according to what criteria"); including stakeholders in decision-making processes eventually by means of external networking (how decisions are made and what resources are shared); and making societal aims explicit ("to what expected effects"). Results also emphasise that the production of social value presents challenges. Research limitations/implications: Results indicate that social responsibility can be created in different ways. This study's analysis, however, is limited to illustrative cases from the specific context of Scotland. First, further research is needed on solutions that contribute to a practical understanding on how social value is produced in a variety of contexts. Second, this research does not address what competences are required to develop such solutions. Finally, in this study, the focus has been mostly on successful cases. More insights on the difficulties and limitations that non-investor-owned organisations face when implementing social responsibility would be needed. Practical implications: The implementation of this study's findings is within the control of practitioners and can be useful to the sector, as it identifies the features and challenges of governance consistent with deep forms of social responsibility. Social implications: The paper identifies forms of organisations that place the creation of social value at their core. In doing so, this study's contribution improves understanding around forms of enterprise that can generate positive impacts for society, so that society can promote them actively. Originality/value: This study's contribution offers unique case studies using a framework that analyses social responsibility in a novel way that is by explaining how non-conventional firms design their governance consistently with the aim of producing value for society and to what extent this is done by including diverse interests coming from a variety of stakeholders.